BESS Revolutionizes Renewable Stability in Indonesia: BESS Merevolusi Stabilitas Energi Terbarukan di Indonesia - Zuhri , Muhamad Saifudin; Jamaluddin, Jamaluddin; Ayuni , Shazana Dhiya; Anshory , Izza (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the integration of Battery Energy Storage Systems (BESS) with Solar Power Plants (PLTS) to enhance electrical grid stability in Indonesia, where 90% of electricity is from fossil fuels. The intermittent nature of PLTS often destabilizes the network, causing frequency hunting or blackouts. Using Etap 12.6 software, simulations showed that adding BESS to hybrid PLTS-PLTD systems significantly mitigates these issues. For instance, a 50% drop in PLTS power without BESS required a 55% increase in PLTD power, but with BESS, this increase was only 34%. Thus, BESS is crucial for stabilizing renewable energy integration and supporting Indonesia’s Net-Zero Emissions goal. Highlights: BESS Stabilizes Power: Reduces impact of PLTS power fluctuations on PLTD. Simulation Insight: 50% PLTS drop increases PLTD by 34% with BESS. Net-Zero Goal: BESS supports Indonesia’s renewable energy and emission targets. Keywords: Renewable Energy, Solar Power, Battery Storage, Electrical Grid Stability, Indonesia